2013
DOI: 10.3109/15569527.2013.832687
|View full text |Cite
|
Sign up to set email alerts
|

Diode laser photocoagulation posterior to the ridge in severe stage 3+ threshold retinopathy of prematurity

Abstract: DLP, posterior to the ridge as an additive treatment in the management of severe Zone II, Stage 3+ threshold ROP patients, is safe and effective; this approach could be used as either the primary treatment, or as the follow-up to failed laser treatment of the avascular retina to halt the progression of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…Most patients have regression after one session of laser but in severe cases this may need to be repeated by making the burns confluent anterior to the ridge or by administering laser posterior to the ridge (O'Keefe et al, 1995, Lee et al, 2004 (Ells et al, 2013, Arvas et al, 2014 where ischemic areas are seen on fluorescein angiography (Kushner et al, 1977, Flynn et al, 1979, Lepore et al, 2014, Lepore et al, 2011. The anterior avascular retina is a result of the interruption of angiogenesis caused by the premature birth but the areas of ischaemic retina behind the ridge as visualized by fluorescein angiography may represent areas of capillary dropout analogous to that occurring in oxygen-induced retinopathy seen in experimental animals where high ambient oxygen causes the loss of already existing capillary beds (Ashton et al, 1953, Patz, 1954, reviewed by Gole (Gole, 1985), and shown in the kitten model by .…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Most patients have regression after one session of laser but in severe cases this may need to be repeated by making the burns confluent anterior to the ridge or by administering laser posterior to the ridge (O'Keefe et al, 1995, Lee et al, 2004 (Ells et al, 2013, Arvas et al, 2014 where ischemic areas are seen on fluorescein angiography (Kushner et al, 1977, Flynn et al, 1979, Lepore et al, 2014, Lepore et al, 2011. The anterior avascular retina is a result of the interruption of angiogenesis caused by the premature birth but the areas of ischaemic retina behind the ridge as visualized by fluorescein angiography may represent areas of capillary dropout analogous to that occurring in oxygen-induced retinopathy seen in experimental animals where high ambient oxygen causes the loss of already existing capillary beds (Ashton et al, 1953, Patz, 1954, reviewed by Gole (Gole, 1985), and shown in the kitten model by .…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…When comparing the methods of single spots and near confluent photocoagulation, the method of dense laser photocoagulation seems to be more effective and safer [23][24][25] . The complications of the CALCR procedure do not vary in principle from the complications that are described in standard methods of treatment with laser and cryocoagulation under the visual control of an indirect ophthalmoscope [12][13][14][15][16]19,20,22 . In particular, we encountered a various extent of retinal and vitreous haemorrhages in all infants in our study group.…”
Section: Discussionmentioning
confidence: 99%
“…There are different views on the direct treatment of the ridge between the vascular and avascular parts of the retina 8,12,[12][13][14][15][16][17][18][19][20] . Near confluent laser photocoagulation, which was used in the CALCR procedure, seems to be more effective than the usage of individual laser spots.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional laser application to the posterior vascular retina (barrage laser) has been reported in the literature. [12345] However, most of these reports are limited to retrospective series with no definitive treatment criteria and treatment was performed in cases with progressive disease unresponsive to conventional laser treatment.…”
mentioning
confidence: 99%